2018
DOI: 10.1111/bju.14483
|View full text |Cite
|
Sign up to set email alerts
|

Erosion rates of 3.5‐cm artificial urinary sphincter cuffs are similar to larger cuffs

Abstract: After 8 years of experience and extended follow-up, the outcomes of the 3.5-cm AUS cuff appear to be similar to ≥4-cm cuffs for effectiveness and rates of urethral erosion. RT patients have a higher risk of cuff erosion regardless of cuff size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…By combining data, the statistical power was significantly increased which could have contributed to the difference in the results. Our results are supported by the recent study of McKibben et al ( 34 ) wherein history of pelvic RT was found to be an independent risk factor for erosions after AUS placement. It is suggested that progressive obliterating endarteritis and tissue atrophy are frequently noted with pelvic RT.…”
Section: Discussionsupporting
confidence: 91%
“…By combining data, the statistical power was significantly increased which could have contributed to the difference in the results. Our results are supported by the recent study of McKibben et al ( 34 ) wherein history of pelvic RT was found to be an independent risk factor for erosions after AUS placement. It is suggested that progressive obliterating endarteritis and tissue atrophy are frequently noted with pelvic RT.…”
Section: Discussionsupporting
confidence: 91%
“…Thereby, this is true for both studies showing the lowest stricture rates in case of AUS erosion. The impact of AUS cuff size on outcomes and complication rates is still discussed ( 25 ), though most authors did not report increased adverse results for the implantation of smaller AUS cuff sizes ( 26 , 27 ). Regarding urethral erosions, our findings together with Agarwal et al might point to a possible influence on urethral erosions and following risk of urethral stricture formation, which needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior bulbar urethral mobilization, in particular, has been demonstrated to be an independent risk factor for AUS cuff erosion when controlling for history of pelvic radiation. 15 By mobilizing the bladder neck distally, there may be less tension on the bulbar urethra from the anastomosis. In our study, of the six patients (50.0%) who had preoperative SUI and the additional four patients (33.3%) who developed de novo SUI after the index procedure, nine patients (75.0%) underwent subsequent placement of an AUS without removal at a mean study follow-up of 19.3 months.…”
Section: Discussionmentioning
confidence: 99%